Identification and Functional Characterization of a Low-Density Lipoprotein Receptor Gene Pathogenic Variant in Familial Hypercholesterolemia - Shu, Hong-Yan; Zhang, Wei; Zheng, Cong-Cong; Gao, Man-Yun; Li, Yong-Cun; Wang, Yan-Gang (Frontiers in Genetics, 2021)
We report a single-point variant of low-density lipoprotein receptor (LDLR) in a Chinese proband with a clinical diagnosis of familial hypercholesterolemia (FH) with a comprehensive functional analysis. Target exome capture-based next-generation sequencing was used for sequencing and identification of genomic variants in the LDLR gene. The expression, cellular location, and function of the mutant LDLR were analyzed. Sequencing of LDLR in FH patients indicated a point variant of single-base substitution (G < A) at a position of 2389 in the 16th exon, which led to a loss of the 16th exon in the LDLR messenger RNA. This genomic variant was found to cause exon 16 deletion in the mutant LDLR protein. Subsequent functional analyses showed that the mutant LDLR was retained in the Golgi apparatus and rarely expressed in the cellular membranes of HepG2 cells. Accordingly, the intake ability of HepG2 cells with the mutant LDLR was significantly reduced (P < 0.05). In conclusion, our results suggest that a mutant with a single-base substitution (c. 2389G > A) in the 16th exon of the LDLR gene was associated with miscleavage of messenger RNA and the retention of mutant LDLR in the Golgi apparatus, which revealed a pathogenic variant in LDLR underlying the pathogenesis of FH.